Preface - Kosiński, W. (Archives of Mechanics, 1997)
The Journal Archives of Mechanics, published bimonthly, has appeared for more than 40 years and is edited by the Institute of Fundamental Technological Research of the Polish Academy of Sciences. The scope of the Journal covers mechanics and physics of continuous media, theoretical and experimental mechanics of solids and fluids, engineering structures, thermodynamics, analytical and computational methods in mechanics.The Editorial Committee invited the Scientific Committee of the XXXI Polish Solid Mechanics Conference - SolMec'96 organized in Mierki, September 9-14, 1996, by the Institute of Fundamental Technological Research and Committee of Mechanics of the Polish Academy of Sciences, to encourage all authors of oral and poster presentations at the SolMec'96, Conference to publish their contributions in special issues of the Archives of Mechanics and Engineering Transactions.